Augmented reality in developing students’ understanding of chemistry triplet: a systematic literature review - Ribič Luka; Devetak Iztok (Chemistry Teacher International)
Augmented Reality (AR) is increasingly finding its way in chemistry education, and it is becoming an important teaching tool to help students understand complex chemical phenomena. Forty-six papers from two databases published between 2018 and 2023 on the implementation of AR in chemistry education with empirical quantitative research design, were analysed. The results show that learning effectiveness is the main objective of AR studies. Technology acceptance questionnaires and achievement tests were the most popular data collection instruments. AR was recognised as a useful and easy to use tool that helps students to improve their learning. However, no study has yet been conducted on effectiveness of AR on students’ understanding of the chemical triplet. Also, some challenges were identified related to technical issues with the AR app and teachers’ resistance to using this technology. Further research is needed to test this technology in different learning settings and with different types of learners.